Personalisation at the Core of Success: Process Evaluation of the LISTEN Randomised Controlled Trial Evaluating a Personalised Self‐Management Support Intervention for People Living With Long Covid. - Leggat, Fiona; Torrens‐Burton, Anna; Sewell, Bernadette; Sevdalis, Nick; Busse, Monica; Domeney, Anne; Parsons, Judith; Abreu, Maria Ines de Sousa de; Jones, Fiona (Health Expectations, 2025)
Background: The development and evaluation of rehabilitation interventions designed to support people with Long Covid (LC) remains an important ongoing priority. Many people with LC experience episodic, debilitating symptoms that can reduce their ability to engage in all areas of activity. The Long CovId personalised Self‐managemenT support co‐design and EvaluatioN (LISTEN) trial co‐designed and evaluated a personalised self‐management support intervention to build confidence and support people to live better with LC. This paper describes the context, implementation, mechanisms of impact and impacts from the LISTEN intervention, in comparison with usual LC services accessed within the National Health Service (NHS). Methods: A mixed methods process evaluation was nested within the LISTEN pragmatic, multi‐site, randomised controlled trial. Data were collected from sites in England and Wales between September 2022 and January 2024. Observations and focus groups with healthcare practitioners (HCPs) delivering the intervention were conducted to assess fidelity. Standardised implementation measures, focussed on intervention feasibility, acceptability and appropriateness, were gathered from HCPs and intervention participants. Semi‐structured interviews were undertaken with a subset of participants across both trial arms. Data were analysed independently using descriptive statistics, or reflexive thematic analyses, and subsequently integrated, drawing upon the Consolidated Framework for Implementation Research v2. Findings: Thirty‐six HCPs participated in the process evaluation, and 197 intervention participants completed standardised implementation measures. Across both trial arms, 49 participants took part in semi‐structured interviews. Six integrated themes were constructed from all data sources describing and illustrating links between the context, implementation, mechanisms of impact and impacts: 'Delivery during uncertainty and ambiguity', 'Diversity and consistency of usual care', 'Drivers for self‐care and the impact of self‐generated expertise', 'Appropriate if unexpected support', 'Personalisation at the core of success' and 'A spectrum of change'. Conclusion: The LISTEN intervention is an appropriate, feasible intervention for participants and HCPs. The intervention can be delivered to a high level of fidelity following training and with ongoing HCP support. Access, receipt and perceptions of NHS LC services were variable. Personalised, relational interventions, such as LISTEN, can foster favourable impacts on confidence, knowledge and activity and are acceptable and strongly recommended within LC rehabilitation services. Patient or Public Contribution: The study was supported by a patient and public involvement and engagement (PPIE) group from project conception to study end. Using their lived expertise, seven people with LC supported accessible recruitment (e.g., materials), data collection (e.g., topic guides), data interpretation (e.g., theme construction and reviewing findings) and dissemination activities (e.g., online webinars). Trial Registration: ISRCTN36407216, registered 27/01/2022.